2023
DOI: 10.1111/evj.13991
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of imprecise sampling time for 10‐ and 30‐min thyrotropin‐releasing hormone stimulation tests in horses

Dante M. Vorster,
Wenqing Wang,
Kate L. Kemp
et al.

Abstract: BackgroundThe thyrotropin‐releasing hormone (TRH) stimulation test is used to diagnose pituitary pars intermedia dysfunction (PPID) using 10‐ or 30‐min protocols. Imprecise sampling time for the 10‐min protocol can lead to misdiagnoses.ObjectivesTo determine the effect of imprecise sampling time for the 30‐min protocol of the TRH stimulation test.Study designIn vivo experiment.MethodsPlasma immunoreactive adrenocorticotropin (ACTH) concentrations were measured 9, 10, 11, 29, 30 and 31 min after intravenous adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…10 Furthermore, the blood collection after 30 min is reported to be less affected by the timing of the sample collection. 8,28,53 Finally, the acute stress seen in a few horses might have also influenced our results, 16,54 especially in horses that were isolated from the herd for fasting.…”
Section: Limitationsmentioning
confidence: 91%
“…10 Furthermore, the blood collection after 30 min is reported to be less affected by the timing of the sample collection. 8,28,53 Finally, the acute stress seen in a few horses might have also influenced our results, 16,54 especially in horses that were isolated from the herd for fasting.…”
Section: Limitationsmentioning
confidence: 91%
“…15,16 Previous work has shown that imprecise sampling time substantially impacts TRH stimulation test interpretation for the 10-min post-TRH time point. 17 Vorster et al 18 assessed the clinical implications of imprecise sampling time on both 10-and 30-min post-TRH sampling time points and found a similar impact of sampling precision for both protocols, further stressing the importance of exact timing when these samples are collected.…”
Section: Update On Ppidmentioning
confidence: 97%